Análises da estrutura da comunidade de abelhas (Hymenoptera: Apoidea) em uma área de caatinga do Maciço de Baturité, Ceará, Brasil - Bezerra, Alessandra de Carvalho (2010)
The great importance of bees as pollinators of several plant species has stimulated many investigations carried out on the organization and structure of their community. This type of study consist of describe the composition, abundance, richness, diversity, temporal variation of bees and their relationship with plants. The object of this study was to know the community structure of bees from an area of caatinga of “maciço de Baturité”, near the city of Caridade - CE. The study was conducted from January to December of 2009 using a systematic sampling method, performed during five consecutive days in five transects previously defined. Totaling 1,18 hours of sampling effort (made by two collectors) bees were captured with an insect net in plants with flowers, between 6:00 and 17:00 h. We collected 2.463 bees from 56 species. The family Apidae (Anthophoridae) was the one with the largest species of 35,71%, while the family Apidae (Apidae) had the highest number of individuals with 81,04% of all bees caught. The exotic species Apis mellifera was the most representative with 29,15% of species collected, followed by Pauper sp. (22,78%). We collected 50 species of plants visited by bees. The family Asteraceae was the most visited by bees and the plant Wedelia scaberrima the species most visited by bees (28 species). The diversity for the total period of bee species visiting the flowers carried by the Shannon index (H ') was 2,53. This value is considered relatively high for the Caatinga. However, for the value of connectance of whole period (8,93) was considered relatively low compared with the amount of possible interactions of the network. Among the 219 interactions observed, 47,03% were concentrated in six species of stingless bees showing the general feature of interactions in this network. Results showed that the bee community in the study area has heterogeneous composition and generalist species with few bees realizing most of the interactions. The comparison of the diversity indices and species accumulation curve for the two seasons (wet and dry) evaluated doesn’t show any significant difference between them. Likewise no difference was observed in composition between the periods for the network of interactions between plant-bee visiting flowers.